Insight into the genetic variability analysis and cultivar identification of tall fescue by using SSR markers - Fu, Kaixin (Hereditas, 2016)
BACKGROUND: Genetic diversity of 19 forage-type and 2 turf-type cultivars of tall fescue (Festuca arundinacea Schreb.) was revealed using SSR markers in an attempt to explore the genetic relationships among them, and examine potential use of SSR markers to identify cultivars by bulked samples. RESULTS: A total of 227 clear band was scored with 14 SSR primers and out of which 201 (88.6 %) were found polymorphic. The percentage of polymorphic bands (PPB) per primer pair varied from 62.5 to 100 % with an average of 86.9 %. The polymorphism information content (PIC) value ranged from 0.116 to 0.347 with an average of 0.257 and the highest PIC value (0.347) was noticed for primer NFA040 followed by NFA113 (0.346) whereas the highest discriminating power (D) of 1 was shown in NFA037 and LMgSSR02-01C. A Neighbor-joining dendrogram and the principal component analysis identified six major clusters and grouped the cultivars in agreement with their breeding histories. STRUCTURE analysis divided these cultivars into 3 sub-clades which correspond to distance based groupings. CONCLUSION: These findings indicates that SSR markers by bulking strategy are a useful tool to measure genetic diversity among tall fescue cultivars and could be used to supplement morphological data for plant variety protection.